2015
DOI: 10.3109/09513590.2015.1056140
|View full text |Cite
|
Sign up to set email alerts
|

High-visfatin levels in women with polycystic ovary syndrome: evidence from a meta-analysis

Abstract: Our results indicate that high-circulating visfatin level is an intrinsic characteristic of PCOS, which suggests visfatin could be a potential biomarker for PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 39 publications
(51 reference statements)
1
18
1
Order By: Relevance
“…Visfatin is a proinflammatory adipokine involved in inflammation, and the upregulation of this adipokine leads to the development of a chronic low-grade inflammatory state. This biomarker has been studied for several inflammatory diseases such as obesity, metabolic syndrome, type 2 DM, polycystic ovary syndrome, and RA, but the findings are controversial [10][11][12][13][16][17][18]. Subsequent studies described visfatin upregulation in several immune cells including monocytes, lymphocytes, dendritic cells and macrophages [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visfatin is a proinflammatory adipokine involved in inflammation, and the upregulation of this adipokine leads to the development of a chronic low-grade inflammatory state. This biomarker has been studied for several inflammatory diseases such as obesity, metabolic syndrome, type 2 DM, polycystic ovary syndrome, and RA, but the findings are controversial [10][11][12][13][16][17][18]. Subsequent studies described visfatin upregulation in several immune cells including monocytes, lymphocytes, dendritic cells and macrophages [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…It is limiting enzyme in nicotinamid adenine dinucleotide (NAD) synthesis and as such known as nicotinamid phosphoribosyl transferase (NAMPT) [8]. Visfatin has been proposed as a new marker of inflammation in diabetes mellitus (DM), metabolic syndrome, polycystic ovary syndrome, coronary artery disease, and rheumatoid arthritis (RA) [9][10][11][12][13]. Visfatin was shown to induce the secretion of proinflammatory cytokines including TNF-α, IL-6 and IL-8,while these cytokins could induce the expression of visfatin [14].…”
Section: Introductionmentioning
confidence: 99%
“…Visfatin — also called nicotinamide phosphoribosyltransferase (NAMPT), or pre-B-cell colony-enhancing factor (PBEF) — is the most abundant adipokine secreted mainly from the visceral fat adipocytes, and it is positively correlated with body mass index (BMI). Visfatin is upregulated during adipocyte differentiation and has insulin-like activity under physiological conditions; hence, elevated visfatin levels have been found to be positive correlated with metabolic syndromes, such as polycystic ovary syndrome [7], type 2 diabetes mellitus (T2DM) [8], and cardiovascular diseases [9]. In addition, visfatin is also one of the inflammatory cytokines and can interact with interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α)[10].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis [153] encompassing a study among 1341 women (695 with PCOS and 646 controls) showed higher visfatin levels in PCOS women without a significant correlation between it and BMI, HOMA-index, and testosterone. The authors concluded that high circulating visfatin can be perceived as a specific characteristic of PCOS, which even presupposes a role for this adipokine as a potential diagnostic biomarker for PCOS [153]. Kowalska et al [154] found higher visfatin levels and a reduced insulin sensitivity in both normal-weight and obese PCOS women in comparison to healthy controls.…”
Section: Visfatinmentioning
confidence: 99%